The Allocation of Burdens in Litigation Between First Nations and the Crown - Posluns, Michael Wilfred (2014)
This thesis is about two inter-related matters: first, the allocation of burdens of proof in litigation between First Nations and the Crown; and, secondly, the reaction or response of the Crown to the Court’s allocations of burdens, as evidenced in the subsequent cases. Since “burdens of proof” refers to matters of fact and evidence, I refer simply to “burdens”, emphasizing that, I mean all the burdens allocated by a Court and which the Court expects the parties to discharge in order for their case to succeed. My initial interest was in the response of the Crown to the allocation of burdens by the Court and related admonitions. In pursuing this matter it became evident that I needed to establish what allocations the Court had set out and what admonitions it had made as regards previous arguments of the Crown. There are two sets of viewpoints that I examine in this paper: The first is the jurisprudential view as to the allocation of burdens in the Aboriginal and treaty rights cases that I discuss here. The second is the more political and policy-based view of the Crown, federal or provincial, as to its burdens of proof and related burdens, such as the duty to consult and to accommodate, previously set out by the Court. This divergence between the Court’s view and the Crown’s and the recurring indications that the Crown does not intend to accept the Court’s view is my primary interest. I will, at times, refer to the Crown’s attitude, exemplified by this divergence as “recalcitrant” and its behaviour as “recidivism”. It is this divergence between the Court’s interpretations and the Crown’s actions and arguments which is my primary interest throughout this discussion. As a lens through which to examine this divergence I review two bodies of literature on theoretical constructs useful in understanding how the Government seeks to shift certain proof burdens onto First Nations parties. The first is the idea of “purposive interpretation” as it is discussed by Chief Justice Dickson and Justice La Forest in Sparrow, and ...